The Generality of Procurement Risks in the Context of Project Management - Mehrad, Aida (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2023)
Project management in engineering, management, and sometimes business has a considerable contribution. Also, its importance can be observable in the risks of procurement. In the current literature review, the researchers endeavor to comprehensively explain all academic and theoretical definitions, history, process, and relations of these two primary and vital variables to make them clear and practical for scholars and those interested in this field. In fact, with this information and knowledge, studying and working in the project management area can be more reasonable and suitable for all interested scholars and those who plan to perform in this area. This study likewise demonstrates the connection between procurement risks and project management and the crucial function of project management in procurement. Typically, educated individuals in this area could also demonstrate better performance and significantly increase the level of process and outcome in project management in this study considered by the researchers.